Effect of multi-tank thermal energy storage, recuperator effectiveness, and solar receiver conductance on the performance of a concentrated solar supercritical CO2-based power plant operating under different seasonal conditions. (15th November 2016) - Osorio, Julian D.; Hovsapian, Rob; Ordonez, Juan C.
Abstract: Renewable energy technologies based on solar energy concentration are important alternatives to supply the rising energy demand in the world and to mitigate the negative environmental impact caused by the extensive use of fossil-fuels. In this work, a thermodynamic model based on energy and exergy analyses is developed to study the transient behavior of a Concentrated Solar Power (CSP) supercritical CO2 plant operating under different seasonal conditions. The system analyzed is composed of a central receiver, hot and cold thermal energy storage units, heat exchangers, a recuperator, and three-stage compression and expansion subsystems with intercoolers between compressors and reheaters between turbines, respectively. From the exergy analysis, the recuperator, the hot thermal energy storage, and the solar receiver were identified as the main sources for exergy destruction with more than 70.0% of the total lost work in the plant. These components offer an important potential to improve the system performance via design optimization. With reference parameters, the system reaches efficiencies of about 18.3%. These efficiencies are increased with a combination of improved design parameters, reaching values of between 26.0% and 29.4%, depending on the season, which are relatively good for CSP plants. Graphical abstract: Highlights: Thermodynamic analyses of a central receiver sCO2 Brayton CSP system are presented. Lost work rates are larger in the recuperator, hot storage, and solar receiver. Seasonal conditions have a strong impact in the system performance. Process efficiencies of up to 29.4% are reached with improved design parameters.